Tourist Ports and Yachting: The Case of Sardinia - Gian Marco Ugolini; Enrico Ivaldi (Revista de Estudios Andaluces, 2017)
The aim of this work is to describe the situation of nautical tourism in one of the largest islands in the Mediterranean through the analysis of the marinas and the sailing habits of the boaters. After outlining the typology, characteristics and functions of the marinas in the introduction, we briefly present the quantitative-qualitative analysis methodology that was carried out through interviews to the stakeholders and subsequent processing of the original information obtained. The presentation of the results concerns the context of Italian ports and then focuses on Sardinia in terms of ports and berths. The discussion, on the other hand, is based on the original analysis of the use of Sardinian ports, the navigation mode of the boaters, including the characteristics of the boats used. In the conclusions, it is emphasized that Sardinia is at the centre of a boating area that extends to the Upper Tyrrhenian Sea, within which it represents a hub and the favourite area for the most important and rich segment of yachts. This, however, does not preclude existing structures from pursuing an improvement in the supply from the point of view of environmental compatibility, of the quality of the services offered and, above all, of a stronger connection to the tourist offer of the hinterlands.